Credit Growth in Emerging Europe : A Cause for Stability Concerns? - Sirtaine, Sophie; Skamnelos, Ilias (World Bank, Washington, DC, 2012)
High credit growth in Emerging Europe, generally considered a sign of catching-up with the "old" Europe, has begun receiving considerable attention among investors and policymakers alike. Given heightened global risks and the demands under the European Union accession process, the need to better understand this high credit growth's drivers, riskiness, and the possible macroeconomic and financial stability consequences is strong. The authors adopt a holistic approach in reviewing the rapid credit growth experienced in the region, examining macroeconomic, financial sector, corporate sector, and asset market consequences and possible vulnerabilities. They consider three possible scenarios-a catching-up with older European countries, a soft landing as experienced by Portugal in the early 2000s, and a hard landing as experienced by Asia in 1997.